Development Strategy of Agroecotourism Tutur’s Coffee - Jojok Dwiridotjahjomo; Ahmad Zainul Arifin; Purnomo Edi Sasongko; Maroeto; Wahyu Santoso (Nusantara Science and Technology Proceedings)
In the era of economic sustainability in Indonesia, coffee commodity is expected to continue to increase foreign exchange for the country, as well as able to provide jobs for the community so that a concept called agro-tourism is needed. The research question asked is how the strategy of development of Agroecotourism Tutur’s Coffee should be done in order to increase the number of tourists who visit at once can compete with other tourist attractions. The SWOT analysis is used to identify the various factors systematically both forces and opportunities, while simultaneously minimizing the weaknesses and threats from the development of the Agroecotourism Tutur’s Coffee. Analysis of the IFE and EFE matrix results in internal strategic factors in the form of strengths and weaknesses and external factors in the form of opportunities and threats. Power that is owned by Agroecotourism Tutur’s Coffee is a beautiful natural panorama, has a coffee processing from seed to ready to serve as a tourist, and the price of entry is cheap. While the weaknesses are owned by government support focus on the cultivation of coffee has not been to the aspect of tourism. On the other hand, the opportunity is owned by popular nature trend and market segment is not limited by age. While the main threat that must be faced until now the concept of a similar tour.